Effects of the addition of high- vs. low-intensity resistance training on top of endurance training in patients with heart failure: preliminary results from a randomized clinical trial. (11th May 2022) - Gojevic, T; Turri Da Silva, N; Gelade, K; Jacobs, G; Pirlotte, R; Tulleneers, B; Kissembeek, B; Duchateau, A; Mullens, W; Hansen, D
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Hasselt University Background: Adding resistance training on top of endurance training is recommended in the rehabilitation of patients with heart failure. However, it is unknown which intensity of resistance training should be preferred. Purpose: To compare the effects of the addition of high- vs. low-intensity resistance training on top of endurance training in patients with heart failure. Methods: Nineteen patients with heart failure were block randomized (by gender and sex) in a combined high-intensity resistance and endurance group (HIG; n=8, age=61±12y, 7 males, LVEF=38±10%) vs. combined low-intensity resistance and endurance group (LIG; n=9, age=68±21y, 8 males, LVEF=38±13%). Patients trained 3x/week for 45 sessions. The resistance exercises were volume-matched between groups and consisted of three sets of leg press, pull down and dip exercises, separated by 30s of rest, done at 55-70% 1RM in HIG vs. 35-40% 1RM in LIG. Both groups did moderate-intense endurance training on a bicycle, cross-trainer, treadmill and arm ergometer for 30 min per training. Maximal oxygen consumption was evaluated with an incremental cardiopulmonary cycling test and muscle strength by 1-RM testing, while quality of life was assessed with the Minnesota questionnaire, and walking distance by a 6-minute walking test. Mann-Whitney U test was used for analyzing differences between groups in all variables and Wilcoxon signed-rank test for evaluating pre-post difference of the entire sample. P values <0, 05 (2-tailed) were considered statistically significant. Results: Training adherence was similar in both groups (LIG vs HIG: 41±6 vs 37±9 sessions, p=0, 370; Table 1). Overall, the intervention improved maximal oxygen consumption, walking capacity and muscle strength (p<0, 05), but the between-group changes in maximal oxygen consumption (LIG vs HIG: 3±2 vs 3±4 ml/kg/min, p=0, 963), quality of life (LIG vs HIG: -8±23 vs -1±5 points, p=0, 931) and muscle strength (LIG vs HIG: Dip 34±34 vs 18±20kg, p=0, 481; Leg press, 66±87 vs 47±53kg, p=0, 486; Pull down, 9±6 vs 9±7kg, p=0, 574) were similar. Conclusion: Adding either high- or low-intensity resistance training on top of endurance training seems equally effective for improving aerobic capacity and walking performance in patients with heart failure. The study is ongoing.